PENGEMBANGAN VIDEO PEMBELAJARAN FISIKA MATERI USAHA DAN ENERGI BERBASIS POWERPOINT - Reski, Andi; Palittin, I D; Astutik, R (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the feasibility of video learning physics for business and energy based on Microsoft Office PowerPoint. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) which is limited to the Development stage. The research instrument used was a validation questionnaire sheet where 3 validators were used to test the feasibility of the material, media, and language. In addition, other research instruments used were in the form of a readability questionnaire that was distributed to students. The data analysis technique uses the Ideal Standards. The results showed that the average score of the feasibility test by the validator was 99.6 with the "Good" category and the results of the readability test by the students were 44.9 with the "Very Good" category, so the learning video developed was included in the appropriate category. to be tested. The product of this research can be used as an independent learning medium for students.